Systematic literature review: implementation of savi learning model (somatic, auditory, visual, and intellectual) to improve students' ability to understand concepts and actively learn mathematics - Triyono, Ageng; Fatmawati, Alfi; Nuryadi, Nuryadi (Universitas Mercu Buana Yogyakarta, 2024)
Conceptual understanding and active participation are two essential elements in establishing a high-quality mathematics learning process. Unfortunately, conventional teaching methods that do not accommodate diverse learning styles often hinder the achievement of both aspects. This study aims to evaluate the effectiveness of the SAVI (Somatic, Auditory, Visual, and Intellectual) learning model through a Systematic Literature Review (SLR) approach in enhancing students' conceptual understanding and engagement. Analysis of fifteen scientific articles reveals that the implementation of the SAVI model consistently produces positive outcomes in achieving learning objectives, both in the cognitive and affective domains. This model has been proven to accommodate various student learning styles, improve classroom interaction, and deepen students’ meaningful understanding of mathematical concepts. Therefore, the SAVI learning model is recommended as an alternative strategy for designing more effective and relevant mathematics instruction.